PENGARUH PELATIHAN PENYUSUNAN LAPORAN KEUANGAN TERHADAP PERSEPSI KEMUDAHAN IMPLEMENTASI AKUNTANSI DAN MANFAAT INFORMASI AKUNTANSI (Studi pada Usaha Mikro Kecil dan Menengah di Kabupaten Jember) - Putri, Nailah Cahaya; Yuliarti, Norita Citra; Martiana, Nina (Relawan Jurnal Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the country's economic movement. Moreover, in the current era, the MSME population is 65.64 million people and is predicted to increase every year. MSMEs experience many obstacles, such as during the pandemic, competition and financial problems. In terms of financial matters, there are still many MSMEs who do not keep accounting records. Lack of knowledge about accounting hinders business management, making it difficult for them to decide which policies to implement. Many entrepreneurs don't understand bookkeeping, which makes accounting decision making difficult. To encourage MSMEs to use accounting, it is necessary to start by fighting the MSMEs themselves. Financial reports are very important for businesses because they can provide relevant and accurate decision making information. Well-prepared financial reports can assist in making strategic decisions and provide a clear picture of a company's financial performance. However, in practice, many challenges arise when preparing financial reports. This research was conducted in Jember Regency with a population of 219 MSMEs and a sample size of 24 MSMEs. The results of this research are that simultaneously training in preparing financial reports (X) has no effect on the perception of ease of implementation of accounting (Y1) and at the same time the benefits of accounting information (Y2).